The Effect of Red Guava Ratio with Lemon and Gelatin Concentration to Quality of Red Guava Marshmallow - Nikita Anastasya Ginting; Herla Rusmarilin; Rona J Nainggolan (Universitas Sumatera Utara, 2014)
The purpose of this study was to determine the effect of red guava ratio with lemon and gelatin concentration of the quality of marshmallow. Method of this study was randomized complete design with two factors, ratio of red guava and lemon (S) (50% : 50%, 60% : 40%, 70% : 30%, 80% : 20%) and gelatin concentration (G) (2,5%, 3%, 3,5%, 4%). The analyzed parameters include moisture content, ash content, ascorbic acid content, total acid, total soluble solid, sensory test (taste, flavor, color and texture). The ratio of red guava and lemon gave a significant different effect on moisture content and gave significant different effect on ash content, ascorbic acid content, total acid, total soluble solid, sensory test taste, flavor, and texture, and had no significant different effect on sensory test color. The gelatin concentration gave a significant different effect on moisture content, ash content, ascorbic acid content, total acid, total soluble solid, sensory test color and texture, and had no significant different on taste and flavor. The interaction of red guava ratio with lemon and gelatin concentration had no significant different effect on moisture content, ascorbic acid content, total acid, total soluble solid, sensory test (color, flavor, taste and texture) but gave a significant different effect on ash content. The best composition which gave the best effect on marshmallow is 80% : 20% of red guava ratio with lemon and 3,5% of gelatin concentration. Keywords : Gelatin concentration, lemon, marshmallow, red guava.